Métodos de conservación de forraje para la alimentación de ganado bovino, en la época seca - Bustamante Piedrahita, Douglas Romario (2023)
In the field of livestock farming and the production of food for livestock, forage conservation techniques of two prominent methods in this field: haymaking and silage, which stands out in this exploration is the preservation of nutritional quality. of the leaves, an essential part of the plant with a high value in the diet of livestock, this document focuses on the exploration of forage conservation techniques, such as haymaking and silage, with the purpose of providing relevant information for the livestock feeding during the dry season. This process highlights the importance of preserving the nutritional quality of the leaves, which are the most valuable part of the plant. Silage is significantly distinguished from haymaking, as it does not rely on dehydration, but on fermentation induced by specific bacteria. This emerging technique is an excellent option for livestock farmers, due to its high nutritional content. In addition, it offers the advantage of prolonged storage, which is beneficial in drought or other situations. Regarding production costs, it is important to mention that both silage and haylage are accessible options for livestock farmers that can demonstrate both economic and environmental benefits, with haylage being more suitable for larger scale livestock farms that require specific machinery for its production. preparation.